Exosomes and Melatonin: Where Their Destinies Intersect - Novais, Adriana Alonso; Chuffa, Luiz Gustavo de Almeida; Zuccari, Débora Aparecida Pires de Campos; Reiter, Russel J. (Frontiers in Immunology, 2021)
Cell-to-cell communication is a complex process associated with regular stimuli to maintain healthy cellular interactions, but which may also result in defective signaling. Exosomes are small membrane25 bound vesicles (30-100 nm) that contain a wide range of functional proteins, mRNAs, and miRNAs potentially interacting with healthy or diseased cells via several molecular means. Melatonin is an indoleamine produced by the pineal gland in a circadian manner; additionally, non-circadian melatonin derives from mitochondria of all normal cells. In addition to exhibiting antioxidant, anti-inflammatory, anti-tumor, and anti-aging activities, melatonin has been recently suggested to stimulate exosomes by modulating their number and/or content load. This review summarizes the relationship between melatonin and exosomes in several pathological processes. We conclude that melatonin associated with exosomes ameliorates inflammation, ischemia-reperfusion injury, degenerative, and neoplastic processes which involve different mechanisms. Melatonin-stimulated exosomes represent a promising therapeutic tool since they are capable of interfering with basic molecular processes, such as oxidative stress and the inflammatory cascade, which underpin many pathophysiological aspects of diseases.